Droplet impact on copper substrate super hydrophobic surface - Choo, Jia Qing (2017)
Ultra hydrophobic (or super hydrophobic) surfaces are known to be incredibly difficult to wet; this is due to the act of cohesion between water molecules and surface. Hydrophobicity also describes the situation where the surface actively repels water from fully contacting the surface. In most materials, this property stems from a variety of micro or nanostructures or a combination of both; the late is known as hierarchical structures. Hydrophobicity generally describes the physical state which allows the contact angle to be greater than 150°. This is generally associated with the interfacial tension between the surface and the liquid, a physical effect. The interest in the hydrophobic physical phenomenon has been steadily gaining steam in the past few years due its potential applications in academic and industrial settings as such the ability to self-clean (i.e. the contaminants deposited on the surface can be easily washed away) or hydrophobic membranes which could allow gases to vent but retain liquids in the container. Research has even proposed that super hydrophobic surfaces can be used to repel the water droplets which form ice on impact or prevent the accumulation of ice. This phenomenon has been termed as icephobicity and is one of the areas of interest for further research. This study aims to demonstrate the effects of changing the effect of current and time on the electroplating process of a copper-based substrate to generate a super hydrophobic surface and using water droplets to impact upon the super hydrophobic surface. By presenting visual representation and numerical analysis of dropping water droplets onto the surface, it can be demonstrated that the current delivered during the electroplating process is of more importance than the time that the copper substrate is exposed to the electroplating process.